Implementasi Pelatihan Self Awareness Sebagai Upaya Meningkatkan Motivasi Belajar: Pengabdian - Kur’ani, Nur; Sugiarto, Nandang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The problem faced by partners is low student learning motivation. The purpose of this community service is to provide students with an understanding of self-awareness and its impact on student motivation that influences the teaching and learning process in the classroom. The partner group for this community service activity consisted of students of SMK Muhammadiyah 1 Pontianak. This research was conducted by using psycho-educational method. Self-awareness training is an effort to increase learning motivation consists of the planning, implementation stages (giving a pre-test, providing material on self-awareness and motivation, giving a post-test) and evaluation. The self-awareness training was attended by 38 students of SMK Muhammadiyah 1 Pontianak. This training started from September 8 to 10, 2025 from 07.00-10.30 WIB in the SMK Muhammadiyah 1 Pontianak Hall. This training activity was carried out in stages for 3 meetings with lecture and practice methods. The target participants in this activity were representatives of 10th and 11th grade students. The results showed an increase in students' knowledge about self-awareness that was signed by changes in students' attitudes after completing the community service.